Policy Promise, Local Practice: Measuring the Impact of Compulsory Schooling on Child Labour in Uttar Dinajpur - Khan, MD.Yehya (Journal of Innovation in Education and Social Research, 2025)
This study examines the effectiveness of compulsory schooling policies in reducing child labour in Uttar Dinajpur, West Bengal, India. Despite legislative frameworks such as the Right to Education Act (2009), child labour remains persistent in rural districts. Using primary survey data from 450 households and secondary enrollment statistics, this research employs quantitative analysis to measure the gap between policy intentions and ground realities. The findings reveal that while school enrollment has increased by 23%, approximately 18% of children aged 6-14 continue to engage in economic activities, particularly in agricultural and informal sectors. The study identifies poverty, parental education, and accessibility as primary determinants affecting policy implementation. The research contributes to understanding the complexities of educational policy implementation in economically disadvantaged regions and provides evidence-based recommendations for policymakers.